Penerapan Malcolm Baldrige untuk Mengukur Kinerja KSPPS BKK Purwokerto - Septianingsih, Leny; Zahrotunnida, Nabila; Aflah, Nafilah; Yuniar , Rifki Nika; Husen, Saadilah Amril; Sulasih, Sulasih (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to evaluate the performance of KSPPS BKK Purwokerto using the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE), which consist of seven assessment categories: leadership, strategy, customer focus, measurement and knowledge management, workforce, operations, and organizational results. A descriptive qualitative approach was employed through in-depth interviews, direct observations, and document analysis. Data were analyzed using the interactive model of Miles and Huberman to identify strengths and weaknesses within the organization. The findings indicate that KSPPS achieved a total score of 825, placing it in the Excellent – Benchmark Leader category. The strongest performance appears in customer focus, leadership, and operational quality, reflecting strong service orientation and solid interpersonal relationships. However, the lowest score in measurement, analysis, and knowledge management suggests that the data and information system is not yet fully integrated. These results highlight the need for improving information systems, digitalizing processes, and strengthening performance measurement to support continuous improvement. This study contributes to the literature on Islamic microfinance performance evaluation and provides strategic recommendations for enhancing organizational management.